Electron dynamics for high-intensity hollow electron beams. (31st March 2021) - Rossi, A.; Nikiforov, D.; Arsentyeva, M.; Barnyakov, A.; Levichev, A.
Abstract: Hollow Electron Lenses (HEL) will be installed at the High Luminosity Large Hadron Collider to provide a continuous and controlled depletion of beam halo particles by interaction with a superimposed hollow electron beam, of intensity as high as 5 A, and radii 1.1–2.2 mm for 7 TeV LHC operations. In this paper, issues related to the propagation of high intensity hollow electron beams are discussed and the simulations of the electron beam dynamics with feedback to the HEL design are presented. The main results are the rise of the electron beam accelerating voltage from 10 kV, as in the initial proposal, to 15 kV and the validation of the 5 T magnetic field at the main solenoids as being sufficient to guarantee a stable electron beam.